Arab traders in their own words - Liebrenz, Boris. (Leiden ; Boston)
ix, 701 sayfa
Keywords: “Arab Traders in their Own Words explores for the first time the largest unified corpus of merchant correspondence to have survived from the Ottoman period. The writers chosen for this first volume were mostly Christian merchants who traded within a network that connected the Syrian and Egyptian provinces and extended from Damascus in the North to Alexandria in the South with particular centers in Jerusalem and Damietta. They lived through one of the most turbulent intersections of Ottoman and European imperial history, the 1790s and early 1800s, and had to navigate their fortunes through diplomacy, culture, and commerce. Besides an edition of more than 190 letters in colloquial Arabic this volume also offers a profound introductory study“ -- Yayıncı.